2010
DOI: 10.1021/ic1009835
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Aromatic Heterocycles with Uranium Alkyl Complexes

Abstract: The reactivity of a uranium dibenzyl complex supported by a ferrocenediamide ligand toward aromatic N-heterocycles was investigated. The uranium dibenzyl complex reacted with 1 equiv of pyridine or picoline to give the respective ortho-metalated product. In turn, the eta(2)-N,C-pyridyl complexes reacted with benzoxazole or benzothiazole, leading to a cascade of transformations that involves C-C coupling of the two heterocyclic rings, ring opening, and alkyl transfer. A similar cascade was previously reported f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…The mechanistic proposal shown in Scheme 1 was supported by the analogous reactions of a pyridylebenzyl complex with benzoxazole and benzothiazole [30] and by the characterization of a CeC coupled product based on 1-methylbenzimidazole [31,36]. This complex, 3 mbi , is analogous to 3 mi (shown in Scheme 1).…”
Section: Resultsmentioning
confidence: 93%
“…The mechanistic proposal shown in Scheme 1 was supported by the analogous reactions of a pyridylebenzyl complex with benzoxazole and benzothiazole [30] and by the characterization of a CeC coupled product based on 1-methylbenzimidazole [31,36]. This complex, 3 mbi , is analogous to 3 mi (shown in Scheme 1).…”
Section: Resultsmentioning
confidence: 93%
“…The electron donating 1,1′-ferrocenediyl group (Sauro and Workentin, 2002) makes the amide donor bind strongly to the highly electropositive group 3 metals and uranium(IV) ion. By using NN TBS as the ancillary ligand for d 0 f n metal alkyl complexes, the C-H bond activation of aromatic heterocycles , successive C-C bond coupling Carver et al, 2010;Monreal and Diaconescu, 2010;Williams et al, 2010), dearomatization of aromatic heterocycles , and the unprecedented ring-opening of 1-methylimidazole Monreal et al, 2009), 1-methylbenzimidazole , or other aromatic heterocycles (Duhović et al, 2010) were observed and studied (Diaconescu, 2010a;Diaconescu, 2010b).…”
Section: Advantages Of 11′-ferrocenediyl Diamide Ligandsmentioning
confidence: 99%
“…[14][15][16] Our group has studied extensively the reactivity of group 3 metals and uranium alkyl complexes supported by diamide ligands towards heterocyclic aromatic compounds. [17][18] Benzyl complexes were found to ring open 1-methylimidazoles, [19][20][21][22][23] effect C-C coupling of pyridines, [24][25] and alkyl transfer to isoquinoline. [26][27] In those cases, the ligand framework was a ferrocenediamide that could support a weak donor-acceptor interaction between the metal in the ligand.…”
Section: Introductionmentioning
confidence: 99%